Interventions for the Public Policy of Social Assistence in CRAS for the Acess of Eventual Benets in Time of Pandemic in the Municipality of Palmas-PR (Emancipação, 2023)
The Public Policy of Social Assistance operationalized in the Social Assistance Reference Centers (CRAS) enables access to eventual benefits in times of the pandemic. The article aims to reflect the interventions in the CRAS for the access to eventual benets by the population in times ofpandemic. The study is articulated by the development of the bibliographic research with the description of the participant observation about the daily work in a CRAS of Palmas-PR. Among the results is the vulnerability of the population aggravated by the pandemic and social assistance becomes the strategic resource for access to  goods and benets for their minimum basic needs. Among the most sought after benets in the CRAS is the basic food basket which confirms that the conditions of poverty, the impact of social isolation, the changes in daily life and work aggravated the conditions that were already present in the population that systematically resorts to social assistance to enjoy the right to non-contributory social protection.